The targeted photodynamic therapy of breast cancer with novel AS1411-indium(III) phthalocyanine conjugates - Akkus, Nurefsan; Eksin, Ece; Sahin, Gamze; Yildiz, Esma; Bagda, Efkan; Altun, Ahmet; Bagda, Esra (Elsevier, 2024)
In the study, the novel indium(III) phthalocyanines containing 4-mercaptopyridine groups as substituents on the peripheral (Pc3) or non-peripheral (Pc8) tetra-and peripheral octa (Pc13) positions were synthesized. After then, the synthesized phthalocyanines were converted to their water-soluble derivatives that are Pc5, Pc10, and Pc15 by the quaternization of the nitrogen atoms on the substituents. These new phthalocyanines have been characterized by various spectroscopic methods such as FT-IR, 1H-NMR, elemental analysis, UV-vis, MALDI-TOF mass spectra. Photochemical properties were also investigated for the synthesized phthalocyanines. In this study; quaternized derivatives were studied in DMSO and aqueous solutions, while non-quaternized derivatives were studied only in DMSO. The interaction between AS1411 and three phthalocyanines (Pc5, Pc10, and Pc15) was investigated using spectroscopic methods and electrochemical impedance spectroscopy technique combined with pencil graphite electrodes (PGEs). The cytotoxic activity of AS1411 and each phthalocyanine was investigated in the MCF-7 and doxorubicin (Dox) resistant MCF-7/DOX-R cell lines in the presence and absence of Dox. The photodynamic therapy (PDT) activity of Pc5, Pc10, and Pc15 and their AS1411 conjugates was investigated on MCF-7, MCF-7/DOX-R and MCF-10A cells. The IC50 values for MCF-7 cells were found as 1.1, 0.46, and 0.46 mM for Pc5 and 0.58, 0.34, and 0.32 mM for Pc5-AS1411 conjugate in the absence of irradiation and radiation with 7 J and 20 J. The values for MCF-7/DOX-R cells were found 0.81, 0.30, and 0.11 mM for Pc5 and 0.39, 0.12, and 0.15 mM for Pc5-AS1411 conjugate without irradiation and radiation with 7 J and 20 J, respectively. Apoptosis and cell imaging studies showed that conjugation of the phthalocyanines with AS1411 induced apoptosis in both cell lines and increases the intracellular entry of phthalocyanine Pc5.
Keywords: Phthalocyanine; Indium; Singlet oxygen; Photodynamic therapy; Electrochemical impedance spectroscopy